Comparison of Ku-Band satellite rain attenuation with ITU-R prediction models in the tropics - Ismail, Ahmad Fadzil; Badron, Khairayu; Yaacop, Afham; Dao, Yao (2013)
Rain attenuated Ku-band beacon signal from Malaysia’s MEASAT satellite was compared with various ITU-R prediction models in the attempt to identify the best applicable technique. The preliminary findings indicate that ITU-R P.618-5 is the best ITU-R model since it offers good estimations that almost comparable to the measured attenuation values. The use of radar-derived parameter namely the local rain height information was observed to contribute a significant improvement to the prediction models